Analytical solution of the time fractional Fokker-Planck equation - Sutradhar, Tumpa; Datta, B.K.; Bera, Rasajit Kumar (Zielona Góra: Uniwersytet Zielonogórski)
A nonperturbative approximate analytic solution is derived for the time fractional Fokker-Planck (F-P) equation by using Adomian`s Decomposition Method (ADM). The solution is expressed in terms of Mittag-Leffler function. The present method performs extremely well in terms of accuracy, efficiency and simplicity.
Keywords: Fokker-Planck equation; Adomian decomposition method (ADM); fractional calculus; fractional differential equations